HOT TOPICS INNOVATIVE INVESTMENT THE DEVELOPMENT OF LANDSCAPING - and (Municipal economy of cities. Series: «Economy science», 2013)
Abstract The possibilities of innovation and the development of investment landscaping, revealed major problems in the formation of a favorable innovation and investment protection. Ways of overcoming the negative processes in the development of gardening.